Language Learning Strategies and Young Learners - Mihaljević Djigunović, Jelena (Array, 2002)
The paper examines young learners' awareness and use of learning styles and strategies in learning English as a foreign language. The author presents the findings of a study carried out with young EFL beginners at different points of language learning. Attention is particularly directed to repors of 6-9 year olds obtained by means of the projection technique. The results are interpreted within the framework of existing insights and current trends in the area of teaching foreign languages to young learners.